A2.10 The isotype and subclass distribution of anti-carbamylated protein antibodies in rheumatoid arthritis patients. (24th February 2016) - van Delft, MAM; Verheul, MK; van der Woude, D; Huizinga, TWJ; Toes, REM; Trouw, LA
Abstract : Background: The presence of auto-antibodies is an important hallmark in Rheumatoid Arthritis (RA). In RA, auto-antibodies can be detected that target post-translationally modified proteins. Next to the well-known anti-citrullinated protein antibodies (ACPA) we have recently identified anti-carbamylated protein antibodies (anti-CarP antibodies). These anti-CarP antibodies are present in 45% of the RA patients and are associated with radiological damage. Anti-CarP is present years before disease onset and predicts the progression to RA in arthralgia patients and healthy blood donors. For better understanding of the antibody response, we determined the anti-CarP isotype and IgG subclass usage in RA patients. Methods: To investigate the presence of anti-CarP IgM, IgA IgG isotypes and IgG subclasses, serum samples of 373 unselected RA patients, 196 healthy controls and 120 disease controls were collected. ACPA data was available for almost all RA patients The presence of anti-CarP antibodies was determined by ELISA. Results: Within RA patients, anti-CarP IgM is present in 16.4% of the subjects, while 49.2% and 40.8% are positive for anti-CarP IgG or IgA, respectively. Interestingly, 24% of ACPA negative RA patients display anti-CarP IgA reactivity. Furthermore, we observed reactivity for all anti-CarP IgG subclasses with 50.7% of patients positive for anti-CarP IgG1, 27.1% for IgG2, 8.0% for IgG3 and 27.3% for IgG4. Moreover, we find that the number of anti-CarP isotypes and IgG subclasses in RA patients is associated with anti-CarP antibody levels. In ACPA and anti-CarP double positive patients we observed that the distribution of isotype and subclass usage differs between the two autoantibody reactivities. In addition also the number of anti-CarP isotypes and IgG subclasses is not obviously related to the number of ACPA isotypes and IgG subclasses in IgG double positive patients. Conclusions: These data show that the anti-CarP antibody response uses a broad spectrum of isotypes and IgG subclasses in RA patients. These data are of relevance for the potential pathological effector mechanisms that can be recruited by the anti-CarP antibody response and possibly the clinical associations associated therewith.